yuhanad, Pengaruh Kualitas Audit dan BOPO terhadap Profitbailitas - Rifan, Dinda Fali; Qintharah, Yuha Nadhirah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
ABSTRACTThis study aims to determine and analyze the effect of Audit Quality and Operating Costs on Operating Income (BOPO) on profitability as measured by Return on Assets (ROA). The research method used is a quantitative approach, with the research population being Islamic Commercial Banks (BUS) in Indonesia and registered with Bank Indonesia for the period 2012-2018. The sample in this study were 6 Islamic Commercial Banks from a total of 14 Islamic Commercial Banks obtained using the purposive sampling method. The sample data was tested using descriptive analysis techniques, while the hypothesis testing was tested using multiple linear regression analysis. The results in this study indicate that the audit quality variable has a negative effect on profitability as measured by ROA and the BOPO variable also has a negative effect on profitability as measured by ROA. In addition, the variables of audit quality and BOPO together have an effect on ROA. Keywords: Audit Quality, BOPO, ROA, Islamic Commercial Bank